The Effect of Organizational Citizenship Behavior (OCB) Towards Work Stress and Performance of Employees in Income Agency Regional City of Denpasar - Sang Putu Krisna Adhi Pranata; Ni Wayan Sitiari; Putu Ngurah Suyatna Yasa (Universitas Warmadewa, 2020)
This research aims was to analyze and determine the effect of OCB on work stress and employee performance at the Denpasar City Revenue Agency. The hypothesis proposed based on theoretical studies and phenomena set forth in the formulation of the problem are 1) OCB has a positive and significant effect on employee performance, 2) OCB has a positive and significant effect on work stress, 3) Job stress has a negative and significant effect on employee performance, 4) Job stress is able to mediate OCB relations to employee performance. The design of this research pattern is oriented towards quantitative data calculation patterns through questionnaires obtained from respondents as many as 35 people, where the items of each question refer to the indicators of each research variable, the data used are primary and secondary data both qualitative and quantitative which then analyzed SEM based on PLS, The results found, 1) OCB has a positive and significant effect on employee performance, 2) OCB has a negative and significant effect on work stress, 3) Job stress has a negative and significant effect on employee performance, 4) Work stress is a mediating variable that connects OCB variables with employee performance.